Flora bacteriana cloacal y nasal de Lepidochelys olivacea (Testudines: Cheloniidae) en el pacífico norte de Costa Rica - Santoro, Mario (2005)
The aerobic cloacal and nasal bacterial flora of 45 apparently healthy female olive ridley sea turtles (Lepidochelys olivacea) was studied at Nancite nesting beach, in Santa Rosa National Park (Costa Rican North Pacific) during July and August 2002. Bacterial samples were obtained by inserting sterile swabs directly into the cloaca and the nasal cavities of the turtles. Ninety-nine aerobic bacterial isolates, including 10 Gram-negative and 5 Gram-positive bacteria, were recovered. The most common bacteria cultured were Aeromonas spp. (13/45) and Citrobacter freundi (6/45) from cloacal samples and Bacillus spp. (32/45), Staphylococcus aureus (6/45) and Corynebacterium spp. (5/45) from nasal ducts. The results of the present study showed that the aerobic bacterial flora of nesting female olive ridleys was composed of several potential human and animal microbe pathogens.